Social Exclusion in Urban Uruguay - Baker, Judy L. (World Bank, Washington, DC, 2012)
This report makes several policy conclusions related to urban poverty and development in Uruguay and potentially the rest of Latin America. First, policies which prioritize improvements in access to quality basic services, particularly education, health, transportation, social assistance, more flexible land use policies, as well as public information for those in marginal areas could help to provide an important link to jobs and human capital development, and reduce some of the facets of social exclusion. New community based programs designed and implemented by neighborhood members based on specific needs, or expansion of existing community programs, could also help to reverse the marginalization process. Second are policies related to housing. Policies that foster the maintenance of traditional integrated neighborhoods, or minimize the concentration of the poor in marginal neighborhoods, may mitigate the exclusion process. Such policies, while politically popular, should be investigated. Finally, the aggregate numbers on inequality appear to mask what is happening at a more disaggregated level such as the neighborhood. While income inequality for the country as a whole only shifted slightly during the 1989-1996 period, the within and between area changes were significant. The results of the analysis also show that polarization is not symmetric - poor individuals are clustering more, but higher income areas still have a higher income variance and more inequality.